The relationship between empowerment and job satisfaction among front-line employees in hotel industry / Siti Nurulhana Abdul Razak - Abdul Razak, Siti Nurulhana (2010)
Empowerment is the perception that workers can help determine their own work roles, accomplish meaningful work, competence in their work and can give impact to the important decisions. A half century of research suggests that empowerment strategies can offer real benefits like will make the employee perform well and also will get job satisfaction. In order to give empowerment to the employees, the manager needs to look at the job tenure of the employees. The dimensions of job tenure are skills and experiences. Hence, it may affect employees’ job satisfaction. Research approach for this study is quantitative which is a set of questionnaires has been developed. This study was conducted to examine the relationship between empowerment and job satisfaction of front- line employees in Kuala Lumpur 3-star hotels. A total of 150 questionnaires were distributed at 10 hotels in Kuala Lumpur, Malaysia. Results showed that empowerment does have significant relationship through the dimensions of meaningfulness, competence self-determination and impact with job satisfaction of the front line employees. Managers certainly need to ensure that employees are satisfied and enjoy what they do at work. By developing creativity and rooms for employees to exercise empowerment, it can enhance their job satisfaction level and performance thus providing quality service to customers.